Peranan Sekuen T1 SPACE Coronal Pada Pemeriksaan MRI Brain Dengan Klinis Epilepsi Lobus Temporal Di Unit Radiologi RSUP Prof. Dr. I.G.N.G. Ngoerah Denpasar - Riana Mageles Lodia Panie; Putu Irma Wulandari; Triningsih Triningsih; Anak Agung Ayu Meidiary (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Magnetic resonance imaging (MRI) is a cross-sectional imaging technique based on the principle of magnetic resonance of hydrogen atoms due to radio frequency (RF) signals with the same frequency as the precession frequency (lamor frequency). MRI at the beginning of its development used a semiconductor magnetic field with a power of 0.5-1.5 Tesla, but now MRI uses a superconductor magnetic field with a power of 1.5-3 Tesla. One of the advantages of brain MRI in epilepsy cases is that it can display clear information about the anatomy and pathology of the head in general in the temporal lobe area. The use of 3D sequences with isotropic voxels such as SPACE (Sampling Perfection With Application Optimized Contrasts With Varying Flip Angle Evolution) is very useful for generating images with high resolution, thinner cuts, and multi-level reconstruction can be performed in several fragments that allow the acquisition of 3D sequences at one time. Methods: The type used is descriptive qualitative research with a case study approach by conducting interviews with 2 radiology specialists, 1 neurology specialist and 3 radiographers related to MRI brain examinations with clinical epilepsy in August-September 2023 in the Radiology Unit of Prof. Dr. I. G. Ngoerah Denpasar Hospital. G. N. G. Ngoerah Denpasar. Results and Conclusion: This study used five (5) patient data who had clinical epilepsy. Based on the results of observations, interviews and documentation in the radiology unit of Prof. Dr. I.G.N.G. Ngoerah Denpasar Hospital, it can be seen that the procedure for examining MRI Brain with clinical epilepsy is that there is no special preparation, only filling out inform consent. The patient is positioned supine on the examination table with a head fixation device with a head first body position and hands beside the body. Radiographers put the patient into the gantry by setting the isocenter i n the middle of the glabella. After positioning the patient the radiographer sets the parameters using axial T2 Turbo Spin Echo (TSE), sagittal T2 Turbo Spin Echo (TSE), coronal T2 Turbo Spin Echo (TSE), axial T2 Turbo Spin Echo (TSE) dark fluit, axial T1 Turbo Spin Echo (TSE) axial Diffusion Weighted Imaging (DWI) and Susceptibility Weighted Imaging (SWI) and coronal T1 SPACE IR isotropic sequences.In addition, the role of coronal slice T1 SPACE sequences is to clearly see the presence of partical dystrophy, to see the thickening or irregularity of the cortex cerebri clearly. In addition, it is also to see the calcification of the temporal lobe and to measure the volume of the hippocampus.